Effectiveness of Integrated Science Learning Materials of Waves in Life by Integrating Digital Age Literacy on Grade VIII Students - Amran, Asrizal Ali; Ananda, Azwar; Festiyed, Festiyed; Yana, Winda Arma (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Literacy skills are important for an educational graduate in 21st century. Integrated science learning is a good method to develop the literacy skills of students. For this reason the 2013 curriculum requires science learning is implemented in integrated pattern. Besides that, ministry of Education and Culture also develop the school literacy movement to improve literacy of students. However, integrated science learning and integrating literacy in learning canât be implemented well. An alternative solution to solve this problem is to use integrated science learning material by integrating digital age literacy. The objective of the research is to investigate the effectiveness of integrated science learning material by integrating digital age literacy in scientific approach to improve the competence of grade VIII students in Junior High School. This research is a part of research and development. The research design which used in preliminary field testing was before and after treatment. Instruments to collect the data in this research consist of three parts namely attitude observation sheet, performance assessment sheet, and learning outcome test sheet. The research data were analyzed by using descriptive statistics analysis, normality and homogeneity test, and paired comparison test. From the data analysis result it can be stated that the use of integrated science learning materials on waves in life theme by integrating digital age literacy is effective in scientific approach to improve three aspects of studentâs competences those are knowledge, attitude and literacy skills.